Isolation, characterization, and nitric oxide production inhibitory activities of the metabolites from the Psidium guava L. in Viet Nam - Van Hieu, Ngo; Cong, Pham Van; Duc, Ngo Viet; Thu Hien, Do Thi; Nam, Duong Thanh; Nhan, Le Van; Tao, Hoang Minh; Trang, Vu Thi; Trung, Nguyen Quang; Dat, Nguyen Tien; Mai, Pham Thi; Tuan Anh, Hoang Le (Vietnam Journal of Science and Technology, 2024)
Thirteen compounds, including catechin (1), gallocatechin (2), quercetin (3), myricetin (4), kaempferol 3-O-α-ʟ-arabinofuranoside (5), avicularin (6), guaijaverin (7), quercetin-3-O-β-ᴅ-galactopyranoside (8), quercetin-3-O-β-ᴅ-glucopyranoside (9), quercetin-3-O-β-ᴅ-glucuronide (10), casuarinin (11), ursolic acid (12), and 4-methoxy-3,5-dihydroxybenzoic acid (13) were isolated from the methanolic extract of the leaves Psidium guajava L. by using various chromatographic techniques. Moreover, the structures of these compounds were continuously elucidated by modern spectroscopic methods (MS, 1H/13C-NMR) and compared with those of the reported data. In addition, all the isolated compounds were futher evaluated for their inhibitory effects on nitric oxide (NO) production in LPS-induced RAW cells with NG-Methyl-L-arginine acetate (L-NMMA) as the positive control. Among of them, compounds 3, 8, 10, and 11 showed inhibitory effects on NO production within IC50 values of 19.30 – 42.86 µM, compared to positive control: IC50 7.90 ± 0.63 µM. Interestingly, compound 13 was first isolated from Psidium guajava L.